2001
DOI: 10.1128/aem.67.8.3340-3349.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects of ntcA Gene Expression and Its Use as an Indicator of the Nitrogen Status of Marine Synechococcus spp

Abstract: Nitrogen nutrition in cyanobacteria is regulated by NtcA, a transcriptional activator that is subject to negative control by ammonium. Using Synechococcus sp. strain WH7803 as a model organism, we show that ntcA expression was induced when cells were exposed to nitrogen stress but not when they were subjected to phosphorus or iron deprivation. Transcript levels accumulated in cells grown on a variety of inorganic and organic nitrogen sources, with the sole exception of ammonium. ntcA transcription was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 53 publications
(65 reference statements)
5
136
1
Order By: Relevance
“…The use of the glutamine synthetase inhibitor MSX indicated that metabolized (as opposed to ambient) ammonium suppressed the transcription of N genes in the Trichodesmium filaments, similar to our findings in marine Synechococcus (Lindell and Post, 2001;Lindell et al, 2005). This is consistent with the concept that a-oxoglutarate accumulates and acts as the NtcA activator molecule when ammonium supplies are limiting Tanigawa et al, 2002).…”
Section: Ammonium Repressionsupporting
confidence: 81%
See 4 more Smart Citations
“…The use of the glutamine synthetase inhibitor MSX indicated that metabolized (as opposed to ambient) ammonium suppressed the transcription of N genes in the Trichodesmium filaments, similar to our findings in marine Synechococcus (Lindell and Post, 2001;Lindell et al, 2005). This is consistent with the concept that a-oxoglutarate accumulates and acts as the NtcA activator molecule when ammonium supplies are limiting Tanigawa et al, 2002).…”
Section: Ammonium Repressionsupporting
confidence: 81%
“…Uptake rates of ammonium often exceed rates of N 2 fixation (Mulholland et al, 2001). Although both organisms thrive in N-depleted environments, N assimilation is thus not as stringently controlled in Trichodesmium as was found in marine Synechococcus (Lindell and Post 2001;Lindell et al, 1998Lindell et al, , 2005. This led us to hypothesize that NtcA control over N assimilation may be principally different in the non-heterocystous filaments of Trichodesmium spp.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations